The numinous universe of books - Escobar, Augusto (Íkala, Revista de Lenguaje y Cultura, 2001)
The author of this essay takes the reader by the hand and leads him/her into the enchanting world of books. For him writing by its very nature indicates a "thirst for knowledge". And like reading, it is a furtive, enigmatic and absorbing pastime.